Pattern Of Religious Guidance Of Nurul Muslimin Mosque Teenagers In Preventing Juvenile Delinquency In Siderejo Hilir Medan Tembung Village - Husain Muhal Tanjung; Muniruddin Muniruddin (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze the pattern of religious guidance applied by the Nurul Muslimin Mosque Youth in preventing juvenile delinquency in Siderejo Hilir Village, Medan Tembung District. This study uses a qualitative approach with a descriptive type of research. Data was obtained through observation, interviews, and documentation involving Mosque Youth administrators, coaches, and adolescents who actively participated in coaching activities. The results of the study show that the pattern of religious guidance applied includes coaching through routine recitation activities, involvement of adolescents in socio-religious activities, providing advice and examples, and habituating religious behavior in daily life. This coaching pattern contributes to increasing awareness of worship, strengthening social awareness, and reducing adolescents' tendency to engage in deviant behavior. Thus, religious coaching carried out by the Youth of the Nurul Muslimin Mosque is one of the preventive efforts in preventing juvenile delinquency through religious and social approaches.